The rise of the superconductors - Ford, P. J. (CRC Press, 2005)
Beginning with the first liquefaction of helium, the book presents the discovery of the Meissner effect and then moves to the key work of Nobel prize-winners Bednorz and Muller. After reviewing the legacy of the last decade, the authors introduce the general structure and properties of superconductors and the organic metals in particular. The final third of the book outlines some major technological advances and suggests future directions, and it examines the impact of theoretical physics on superconductors. Rise of the Superconductors concludes with a brief look at the struggle for technical superiority between the U.S. and Japan, and the influence Europe has had on the development of superconductors.